2010
DOI: 10.7863/jum.2010.29.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Steal of the Portal Vein After Orthotopic Liver Transplant

Abstract: Spontaneous splenorenal shunts (SSRSs) are portosystemic connections between the splenic vein and the left renal vein (LRV) that develop commonly in patients with portal hypertension. (1) They reportedly occur in 18% to 19% of patients evaluated for a liver transplant. (2),(3) As the liver become more cirrhotic, a major steal phenomenon may occur, whereby blood is shunted from the high-resistance venous bed of the liver to the lower systemic pressure of the LRV. (4) Not infrequently, an SSRS will go undetected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 13 publications
0
28
0
2
Order By: Relevance
“…Based on concerns for inadequate hepatic allograft perfusion and hepatic encephalopathy due to persistent portosystemic shunting, intraoperative SSRS ligation during LT has been explored using a variety of surgical techniques . These case series observed that SSRSs frequently persisted after LT, particularly when larger than 10 mm, reported an increase in portal vein flow after shunt ligation, and documented the relative safety of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on concerns for inadequate hepatic allograft perfusion and hepatic encephalopathy due to persistent portosystemic shunting, intraoperative SSRS ligation during LT has been explored using a variety of surgical techniques . These case series observed that SSRSs frequently persisted after LT, particularly when larger than 10 mm, reported an increase in portal vein flow after shunt ligation, and documented the relative safety of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, high blood flow through an SSRS could result in a “portal steal” phenomenon that deprives the already injured liver of blood, oxygen, and nutrients, accelerating disease progression and increasing the risk of adverse liver outcomes. The latter effect has led to postulation that SSRS ligation should be considered in patients undergoing liver transplantation (LT) to prevent ischemic injury to the allograft, particularly if portal inflow is suboptimal based on Doppler ultrasound …”
Section: Introductionmentioning
confidence: 99%
“…1,2,5,8,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] Possible treatment options include preoperative further selective shunting of flow such as transjugular intrahepatic portosystemic shunts, intraoperative assessment of portal flow with a decision to intervene if there is evidence of inadequate flow to the allograft, automatic intraoperative ligation of the shunt, close monitoring of the shunt and the functional status of the transplant liver without intervention, creation of portorenal anastomosis in the case of portal vein thrombosis, or postoperative percutaneous interventions to embolize a symptomatic shunt. …”
Section: Interventionmentioning
confidence: 99%
“…Intraoperative measurements of portal flow in the transplanted liver can guide intervention. 14 The degree of steal from the SRS can be measured quantitatively by occluding the shunt and determining the increase in flow through the portal system of the allograft.…”
Section: Intraoperative Interventionmentioning
confidence: 99%
“…Vascular steal phenomenon directing portal flow away from the graft may occur when large pre-transplant portosystemic shunts, commonly splenorenal, are not ligated at the time of transplant. [16] In vascular steal, the portal venous flow may have decreased velocity or variable direction. A pulsatile portal venous waveform may be normal in the early post-operative period.…”
Section: Introductionmentioning
confidence: 99%